The Role of Legal Aid Institutions in Providing Legal Aid for Suspects and Defendants - Setiani, Syalis Mei (Faculty of Law Universitas Negeri Semarang, 2021)
Indonesia is a state of law, one of which is equality before the law. One of the forms is the existence of legal aid institutions to protect human rights. In this case, it is the suspect/defendant whose rights are often violated due to the arbitrariness of the legal apparatus from arrest to trial. Even though legal rules and codes of ethics have been regulated, every law enforcement officer cannot guarantee that the rights of the community, especially suspects and defendants, are fulfilled. So that this legal aid institution takes the role so that people's rights, both legal protection, legal assistance, good treatment can be accepted by suspects or defendants, so that arbitrariness does not occur. For this reason, legal aid institutions recruit advocates, paralegals, lecturers, and law students to participate in implementing legal aid. Legal aid is given to the poor but does not rule out the possibility of giving it to children, persons with disabilities, women, the elderly, Indonesian workers, or other vulnerable people or groups in accordance with their regional context and regulated in laws and regulations. The suspect himself must be given to the suspect who is threatened with imprisonment of more than 5 years and is incapacitated or is threatened with a sentence of 15 years or death. Otherwise, the claim is considered invalid.